Familial female and male germ cell cancer. A new syndrome? - Galani, E.; Alamanis, C.; Dimopoulos, M.A. (Gynecologic Oncology, 2005)
A small percentage of germ cell tumors is known to be familial. There are several reports describing familial cases of testicular germ cell tumors; however, there are only a few of them reporting germ cell tumors that occurred in both males and females of the same family. We present a family with three children, two females and one male, previously healthy, who all developed germ cell malignancies. The first sibling was diagnosed with malignant teratoma of the ovary, the second one with dysgerminoma involving both ovaries, and the male one with both embryonal carcinoma and seminoma of the testicle. Our case report suggests that the possibility of an association between germ cell tumors of both ovaries and testis should be considered. © 2004 Elsevier Inc. All rights reserved.
Keywords: Embryonal carcinoma; Familial germ cell tumors; Malignant teratoma